2012
DOI: 10.1111/j.1553-2712.2012.01315.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of 6.6 Million Knee Injuries Presenting to United States Emergency Departments From 1999 Through 2008

Abstract: Background: While knee injuries are treated by a wide range of clinicians, patients with knee injuries frequently present to emergency departments (EDs). The knee is the most commonly injured joint by adolescent athletes with an estimated 2.5 million sports-related injuries presenting to EDs annually.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
101
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(104 citation statements)
references
References 32 publications
(54 reference statements)
1
101
2
Order By: Relevance
“…Over 4 billion dollars are spent annually on arthroscopic knee surgery alone (Gage, McIlvain, Collins, Fields & Comstock, 2012) despite evidence suggesting arthroscopic surgery does not result in superior patient outcomes (Kirkley et al, 2008;Sihovnen et al, 2013;Thorlund, Juhl, Roos & Lohmander, 2015). Osteoarthritis (OA) related knee pain has been identified as a possible trigger for physical and functional decline for older adults (Jinks, Jordan & Croft, 2007).…”
Section: Overview Of Problemmentioning
confidence: 99%
“…Over 4 billion dollars are spent annually on arthroscopic knee surgery alone (Gage, McIlvain, Collins, Fields & Comstock, 2012) despite evidence suggesting arthroscopic surgery does not result in superior patient outcomes (Kirkley et al, 2008;Sihovnen et al, 2013;Thorlund, Juhl, Roos & Lohmander, 2015). Osteoarthritis (OA) related knee pain has been identified as a possible trigger for physical and functional decline for older adults (Jinks, Jordan & Croft, 2007).…”
Section: Overview Of Problemmentioning
confidence: 99%
“…There is increased incidence among adolescents and young adults, as well as the growing sporting population. 1 The ACL is the most frequently injured structure. 2 This is often an isolated injury that can be reconstructed with high patient satisfaction and low failure rates.…”
mentioning
confidence: 99%
“…Between 1999 and 2008, the United States Emergency Department estimated 2.5 million sports-related knee injuries annually [3]. Knee sprains and strains were amongst the most common diagnosis (42.1%) and the highest injury rate was amongst those age 15 to 24 years of age [3].…”
Section: Introductionmentioning
confidence: 99%
“…Knee sprains and strains were amongst the most common diagnosis (42.1%) and the highest injury rate was amongst those age 15 to 24 years of age [3]. A separate 10-year study on athletic knee injuries assessed 17,397 patients with sports injuries and found 20% involved the anterior cruciate ligament (ACL), 10.8% involved the medial meniscus, 7.9% involved the medial collateral ligament (MCL), 3.7% involved the lateral meniscus, 1.1% involved the lateral collateral ligament (LCL), and 0.65% involved the posterior cruciate ligament (PCL) [4].…”
Section: Introductionmentioning
confidence: 99%